Perancangan Dan Implementasi Antarmuka Dan Pengalaman Pengguna (UI/UX) Pada Website E-Commerce Furn - Firman Anugrah; Somantri (Jurnal Sains Informatika Terapan, 2026)
This study focuses on the design and implementation of User Interface (UI) and User Experience (UX) for the FURN e-commerce website at PT Nugraha Kreasi Digital to improve user convenience and overall shopping experience. The research applies an interactive design method with a qualitative descriptive approach, involving reference studies, needs analysis, wireframe development, user interface design, interactive prototyping, and design evaluation. The result is an interactive website prototype with clear navigation, consistent visual design, and intuitive user interaction, supported by features such as the BIG Menu, Call to Action (CTA) buttons, shopping cart, and catalog filtering. The design emphasizes usability, responsiveness, and visual consistency to ensure accessibility across different devices and user scenarios. This study is expected to serve as both an academic contribution and a practical reference for developing user-centered UI/UX designs on e-commerce websites.